Specificities of Sanfilippo A syndrome laboratory diagnostics - Trofimova, N.S.; Olkhovich, N.V.; Gorovenko, N.G. (Вiopolymers and Cell, 2014)
Mucopolysaccharidosis type IIIA (MPS IIIA) occurs due to the deficiency of lysosomal enzyme heparan-N-sulfatase (sulfamidase), which is caused by mutations in the SGSH gene. Aim. To identify the characteristics of biochemical diagnosis of MPS IIIA and determine the prevalence of major mutations R74C and R245H in the SGSH gene in Ukrainian patients. Methods. After all the required phases of laboratory diagnosis of this disease, the diagnosis of MPS IIIA was confirmed in 12 patients from 12 families. The level of sulfamidase activity in leukocytes did not exceed 36 % of the control in all patients. Due to very low sulfamidase activity in leukocytes it is sometimes difficult to interpret the results of the analysis which may lead to false-negative or false-positive diagnosis of MPS IIIA. Results. The analysis of the results of molecular investigation of the patients' samples showed that the incidence of mutation R74C was 17/24 (70.8 %), the incidence of mutation R245H was 2/24 (8.3 %). The total incidence of major mutations R74S and R245H among the patients with MPS IIIA in Ukraine was the highest among European countries – 11 out of 12 patients, these mutations were found in at least one allele. Conclusions. Given very high prevalence of major mutations R74S and R245H in the SGSH gene among the patients with MPS IIIA in Ukraine – 79.1 % – it is appropriate to have the screening of mutations in the diagnostic algorithm along with the definition of biochemical sulfamidase activity to prevent false-negative or false-positive diagnosis of Sanfilippo syndrome A. Мукополісахаридоз типу ІІІ А (МПС ІІІ А) обумовлений дефіцитом лізосомного ферменту гепаран-N-сульфатази (сульфамідази), який виникає внаслідок мутацій в гені SGSH. Мета. Встановлення особливостей біохімічної діагностики МПС ІІІ А та визначення розповсюдженості мажорних мутацій R74C і R245H в гені SGSH у пацієнтів з України. Методи. Біохімічні та молекулярно-генетичні. Результати. Діагноз МПС ІІІ А підтверджено у 12 пацієнтів. У всіх обстеженних осіб рівень активності сульфамідази в лейкоцитах крові не перевищував 36 % від контролю. Аналіз результатів проведеного молекулярного обстеження пацієнтів з МПС ІІІ А показав, що частка алелів, які несуть мутацію R74C, виявилася найбільшою і становить 17/24 (70,8 %). Частка алелів з мутацією R245H у обстежених пацієнтів із синдромом Санфіліппо А дорівнює 2/24 (8,3 %). Сумарна частота мажорних мутацій R74С і R245H серед пацієнтів з МПС ІІІ А з України була найвищою з-поміж європейських країн – у 11 з 12 пацієнтів ці мутації зареєстровано хоча б в одному алелі. Висновки. Зважаючи на дуже високу частоту мажорних мутацій R74С і R245H в гені SGSH серед пацієнтів з МПС ІІІ А з України – 79,1 % – доцільно використовувати скринінг таких мутацій в діагностичному алгоритмі паралельно з біохімічним визначенням активності сульфамідази для запобігання хибнонегативної або хибнопозитивної діагности- ки синдрому Санфіліппо А. Мукополисахаридоз типа ІІІ А (МПС III А) обусловлен дефицитом лизосомного фермента гепаран-N-сульфатазы (сульфамидазы), возникающего в результате мутаций в гене SGSH. Цель. Установление особенностей биохимической диагностики МПС ІІІ А и определение распространенности мажорных мутаций R74C и R245H в гене SGSH у пациентов с Украины. Методы. Биохимические и молекулярно-генетические. Результаты. Диагноз МПС ІІІ А подтвержден у 12 пациентов. У всех обследованных лиц уровень активности сульфамидазы в лейкоцитах крови не превышал 36 % от контроля. Анализ результатов проведенного молекулярного обследования пациентов с МПС ІІІ А показал, что доля аллелей, несущих мутацию R74C, оказалась наибольшей и составляет 17/ 24 (70,8 %). Доля аллелей, несущих мутацию R245H, равна 2/24 (8,3 %). Суммарная частота мажорных мутаций R74С и R245H среди пациентов с МПС ІІІ А из Украины была самой высокой среди европейских стран – у 11 из 12 пациентов эти мутации обнаружены хотя бы в одном аллеле. Выводы. Учитывая очень высокую частоту мажорных мутаций R74С и R245H в гене SGSH среди пациентов с МПС ІІІ А из Украины – 79,1 % – целесообразно использовать скрининг таких мутаций в диагностическом алгоритме параллельно с биохимическим определением активности сульфамидазы для предотвращения ложноотрицательной или ложноположительной диагностики синдрома Санфилиппо А.